Adaptive governance of disaster preparedness? The case of regional networks in Finland - Nikkanen, Maija; Räsänen, Aleksi; Juhola, Sirkku (Elsevier, 2024)
Adaptive governance (AG) has emerged as a theoretical alternative to traditional forms of governance, which often fail to address complexity and rapid changes in socioecological systems. Frequently recognized attributes of AG include learning and experimentation, collaboration and networks, polycentric institutions and multilevel governance at multiple appropriate scales, as well as reflexivity, flexibility and adaptive capacity. To provide more examples of the practical implementation of AG, we examine whether a Finnish regional preparedness network model could be an example of a tangible way to implement AG. According to our results, the regional networks embody many features of AG: they facilitate person- and organization-level networking and peer learning, and thus help their members to grasp the overall picture of preparedness and safety in the region, and reveal ambiguities concerning the division of responsibilities. The networks also support nestedness and polycentricity through cross-sector and multilevel cooperation. At the same time, the voluntary nature of the networks is perceived as problematic considering the overall preparedness of society. Notably, although networks often include non-state actors, citizens remain outside of them, which may reduce the effectiveness of a network.
Keywords: adaptive governance; comprehensive security; preparedness; networks; Finland